Analisis Saluran Pencernaan Ikan Katung (Pristolepis grootiiBleeker) di Danau Pekak Desa Buluh Nipis Kecamatan Siak Hulu Kabpaten Kampar Provinsi Riau - Gultom, Imelda Sofia Loren; Putra, Ridwan Manda; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTPristolepis grootii is one of freshwater fishes that inhabit the Pekak Lake in Kampar Regency. A research aim to understand the information of stomach content and its relation with size, sex and environmental condition. This research has been done on November to January 2018. Fish samples were captured using fish trap and rawai. Sampling was conducted 4 times in two months.Type of food present in the stomach content of fish was analyzed and the IP (Index Propenderence) was calculated. There were 62 fishes captured. Result shown the feed of P. grootii consist of insects, plants, phytoplankton, and unidentified organism. The main food of P. grootii was insect (IP 50.57%) and plants remains such as seeds (IP 45.42%). Small fishes (43-52 mm), tend to eat more insect (IP 64.75%), while the medium and big fish (73-103 mm) feed on insect and plants.There are no differences of main food in male and female fishes.The water quality parameter are as follows : temperature 30,50C, brightness 76.25 cm, depth 3- 5 m, pH 6, DO 6.44 mg/L, CO2 9,74 mg/L, nitrate 0.2521 mg/L and Phospate 0.1504 mg/L. Based on data obtained, it can be concluded that the Pristolepis grootii is an omnivorous fish. Keywords : Pristolepis grootii, Stomach Content Analysis, Preponderence index, Pekak Lake.